Comparison of Skin Stapling Devices and Conventional Skin Closure Following General Surgical Procedures - Liaquat, Affifa; Ammar, Ahmed Siddique; Abdul Hannan; Maham Ghaffar; Azwa Janjua (Indus Journal of Bioscience Research, 2025)
Introduction: Wound closure is a critical aspect of surgical procedures, impacting healing, infection rates, and patient recovery. Skin stapling and conventional suturing are commonly used techniques, each with distinct advantages and limitations. This study aims to compare these methods in terms of closure time, postoperative pain, and surgical site infection rates to provide evidence-based guidance for optimal wound closure practices. Methodology: The study, conducted at Mayo Hospital, Lahore, from July 3, 2024, to January 2, 2025, included 120 patients undergoing general surgical procedures. Patients were randomized into two groups: Group A (stapling, n=60) and Group B (sutures, n=60). Standardized preoperative and intraoperative protocols were followed, and data on closure time, pain scores, and surgical site infections (SSI) were collected. Analysis was performed using SPSS version 24, with chi-square and t-tests to compare outcomes. Results were considered significant at p ≤ 0.05. Results: The study demonstrated significant differences in outcomes between the two groups. Skin stapling (Group-A) resulted in a significantly shorter closure time (4.62 ± 1.10 minutes) compared to conventional suturing (Group-B) (11.57 ± 2.06 minutes, p=0.001), indicating greater efficiency with stapling. However, stapling was associated with a higher rate of surgical site infections (26.7% vs. 11.7%, p=0.037), suggesting an increased risk of complications. Additionally, patients in the stapling group reported lower pain scores (3.55 ± 0.80) compared to the suturing group (5.02 ± 0.58, p=0.001). Conclusion: Skin stapling provides faster closure and reduced pain but is associated with a higher risk of surgical site infections compared to conventional suturing. Careful consideration is required to balance efficiency and patient safety when choosing the closure method.